The Optimal Layout of Electrical Interconnection and Transmission Systems of Offshore Wind Farms - Sedighi, Mohsen (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2017)
Off-shore Wind Farm (OWF) is the largest renewable energy resource. The cost of electrical interconnection and transmission systems of OWFs is a considerable fraction of the overall design cost of the farm. In order to minimize the investment and operational costs, this thesis proposes an optimization formulation to find the optimal electrical interconnection configuration of Wind Turbines (WTs) and the optimal size of cables cross section (cable sizing) simultaneously, while the transmission system and other relevant components are optimized as well (e.g. the offshore platforms, offshore substation transformers, switchgears). This simultaneous minimization of total trenching length and cable cross sections creates a complex optimization problem that is solved by the Harmony Search (HS) algorithm. The optimization performance of HS has been compared with the genetic algorithm. The proposed simulations can be applied to a symmetric or asymmetric topology of OWF, which are applied in two case studies. In the first case study, two distinct methods of full and partial optimal cable sizing have been considered to comprehensively assess the optimal interconnection layout of OWFs. Furthermore, various shipping and burying costs as well as various WTs power rating have been considered to investigate their impact on the layout of optimal electrical interconnection system. In the second case study, the optimal layout of electrical interconnection, transmission system and other relevant components of a real OWF have been found simultaneously. In order to demonstrate higher performance of the proposed optimization method and formulation, the results have been compared with another study, where a real OWF has identically been assumed to have a fair comparison, under identical conditions and constraints. The comparison results reveal that, our proposed optimal interconnection system reduces the interconnection cost, cable length and power loss of OWF. Keywords: Off-shore Wind Farm (OWF), optimal interconnection configuration, cables cross section, transmission system, Harmony Search (HS) algorithm, and simultaneous optimization.

ÖZ: Kıyı ötesi rüzgar çiftliği en büyük yenilenebilir enerji kaynağıdır. Bir rüzgar çiftliğinin elektriksel bağlantı ve iletim maliyeti, çiftliğin toplam tasarım maliyetinin önemli bir oranıdır. Bu çalışma, yatırım ve işletme maliyetlerini en aza indirgeme amacıyla, eniyi elektriksel bağlantı yapılandırması ve eniyi kablo boyutlarını, iletim sistemini ve diğer ilgili elektriksel bileşenleri de eniyileştirme hedefli bir eniyileştirme formülasyonu önermektedir. Toplam hendek uzunluğu ve kablo boyutlarının eşzamanlı enaza indirgenmesi, “Uyumluluk Arayışı” algoritması kullanılarak çözülen karmaşık bir eniyileştirme problem yaratmaktadır. Uyumluluk Arayışı algoritmasının eniyileştirme başarımı genetik algoritması ile karşılaştırılmıştır. Benzetimler simetrik ve simetrik olmayan rüzgar çiftliği topolojilerine uygulanabilir. Bu topolojilerin iki farklı durumu üzerine çalışma yapılmıştır. Birinci durum çalışmasında, kıyı ötesi rüzgar çiftliğinin eniyi bağlantı düzeninin kapsamlı bir değerlendirmesini yapmak amacıyla, tam ve kısmi kablo boyutlandırmasından oluşan iki farklı yöntem üzerinde durulmuştur. Buna ek olarak, farklı taşıma ve gömme maliyetleri ile rüzgar türbinlerinin güç kapasiteleri de, eniyi elektriksel bağlantı sistemi üzerindeki etkilerini araştırmak amacıyla ele alınmıştır. İkinci durum çalışmasında, gerçek bir kıyı ötesi rüzgar çiftliğine ait elektriksel bağlantının eniyi düzeni, iletim sistemi ve diğer ilgili elektriksel bileşenleri de eşzamanlı bulunmuştur. Önerilen eniyileştirme yöntemi ve formülasyonunun daha üstün başarımını gösterme amacıyla, gerçek bir kıyı ötesi rüzgar çiftliğini esas alan başka bir çalışma ile karşılaştırmalar yapılmıştır. Karşılaştırma sonuçları önerilen eniyi bağlantı sisteminin, bağlantı maliyetini, kablo uzunluğunu ve rüzgar çiftliğinin güç kayıplarını azalttığını ortaya çıkarmıştır. Anahtar Kelimeler: Kıyı ötesi rüzgar çiftliği, eniyi bağlantı yapılandırması, kablo boyutlandırma, iletim sistemi, Uyumluluk Arayışı algoritması, Eşzamanlı eniyileştirme.
Doctor of Philosophy in Electrical and Electronic Engineering. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2017. Co-Supervisor: Assoc. Prof. Dr. Murat Fahrioğlu, Supervisor: Prof. Dr. Osman Kükrer.
Keywords: Electrical and Electronic Engineering; Renewable energy sources--Wind Energy--Wind power; Electric power transmission--Electric power transmission; Off-shore Wind Farm (OWF); optimal interconnection configuration; cables cross section; transmission system; Harmony Search (HS) algorithm; and simultaneous optimization